Promoting and sustaining a quality teacher workforce - LeTendre, Gerald K.; Wiseman, Alexander W. 1968- (Emerald, 2015)
Teacher effectiveness and teacher quality have become the focus of intense international attention and concern. Around the world, governments are modifying existing certification requirements or implementing value-added modeling in order to qualify teachers without planning for the long-term consequences of these actions. The book brings together scholars from multi-disciplinary and international backgrounds to address two critical areas: (1) what existing cross-national measures of teacher effectiveness and teacher quality are most promising, and how can these be aligned to maximize their research potential; and (2) what core constructs of teacher quality or effectiveness are missing, and how can cross-national research help identify these. Identifying both what is used and what is missing in the international and comparative analysis and reform of teacher quality is key to informing evidence-based educational policy formation around teacher quality.
Includes index.